The Association between Thyroid Function with Bone Mineral Density in Hyperthyroid Patients at The Diabetic Center Clinic of RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar - Katrin Wilentina Siahaan; Made Ratna Saraswati (PT Dexa Medica, 2026)
Hyperthyroidism is a pathological condition caused by an excess of thyroid hormones synthesized and secreted by thyroid gland. The prevalence of hyperthyroidism remains significant worldwide. Hyperthyroidism affect both the resorption and formation phases by stimulating the activity of osteoblasts and osteoclast, shortening the bone remodeling time, and consequently leading to bone loss characterized by a decrease in bone mineral density (BMD). Identifying the risk of osteoporosis and fractures in the hyperthyroid population requires research on the phenomenon of low bone mineral density values in hyperthyroid patients. Therefore, this study seeks to examine the association between thyroid function (TSHs and FT4) with BMD values in hyperthyroid patients. The observational analytic study with a cross-sectional design was conducted on hyperthyroid patients undergoing outpatient treatment at the Diabetic Center Clinic at Prof. Dr. I.G.N.G. Ngoerah General Hospital, Denpasar, from January to May 2024, based on the inclusion and exclusion criteria, aged 18-50 years. This study evaluated TSHs and FT4 levels against BMD using dual-energy x-ray absorptiometry (DEXA) bone scans on the femur and lumbar regions, expressed in Z-scores. Data were analyzed using SPSS v.23.0 through univariate and bivariate analysis. The analysis used Spearman correlation with p<0.05 considered significant. The median age of hyperthyroid patients in this study was 34 years (19-50) years, with 84.4% being women. The TSHs level was 0.22 ± 0.45 mIU/L and the FT4 level was 3.22 ± 3.16 ng/dL. Spearman correlation showed no correlation between TSHs levels (r=0.138; p=0.452) and a negative correlation between FT4 levels (r=-0.426; p=0.015) with the average BMD (Z-score), indicating that the higher FT4 levels, then the bone mineral density value gets lower in hyperthyroid patients. This study demonstrates association between FT4 levels and bone mineral density in hyperthyroid patients, while TSHs levels showed no association with BMD in hyperthyroid patients.